Competition and Regulation as a Means of Reducing CO₂ Emissions: Experience from U.S. Fossil Fuel Power Plants - Christian Growitsch; Simon Paulus; Heike Wetzel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In this article, we analyze the relative CO2 emission performance across 48 states in the U.S. using a two-stage empirical approach. In the first stage, we identify the states that followed best practice by applying benchmarking techniques. In the second stage, we regress our CO2 emission performance indicators on the state-specific national gas prices, the states' CO2 regulatory policies and a number of other state-specific factors in order to identify the main drivers of the developments.
Keywords: C61; D24; L94; Q58; 330